PENGARUH EDUKASI GIZI TERHADAP PENINGKATAN PENGETAHUAN IBU DALAM PENYUSUSNAN MENU BALITA DI WILAYAH PKM MEDAN DENAI TAHUN 2025 - Indra Agussamad; Eko Murdianto; Mesrida Simarmata; Erika Erika; Tahan Tahan; Linda Mardianti Waruwu; Ribka Huta Julu (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
optimal development and preventing the risk of stunting. Mother's knowledge in compiling a toddler menu is a key factor in the practice of fulfilling children's daily nutrition.Objective: To determine the influence of nutrition education on increasing maternal knowledge in the preparation of the toddler menu in the Medan Denai PKM area.Methods: This study used a quasi-experimental design with pre-test and post-test approaches in the intervention and control groups. The sample consisted of 100 mothers who had toddlers aged 6–24 months and were selected through purposive sampling. The intervention group received nutrition education for 3 sessions over a four-week period. Data collection was carried out through knowledge questionnaires before and after the intervention. Data analysis used paired t-test, independent t-test, and ANCOVA. Results: There was a significant increase in knowledge scores in the intervention group (p0.001), while the control group showed a non-significant increase (mean p=0.08). Bivariate and multivariate analyses showed that nutrition education had a significant effect on improving maternal knowledge, regardless of education and family income (p0.001). Conclusion: Nutrition education has been proven to be effective in increasing mothers' knowledge about the preparation of the toddler menu. It is necessary to implement nutrition education routinely in the Puskesmas and Posyandu as a preventive and promotive effort in improving the nutritional status of toddlers. Keywords: Nutrition, Knowledge, Toddler Menu